Correlation between orthopaedic and radiographic examination findings and arthroscopic ligament fibre damage in dogs with cruciate ligament rupture. Issue 12 (29th September 2019) - Ashour, AE; Hoffman, CL; Muir, P
Abstract : Objective: The objective is to study the correlations between physical examination and stifle radiography findings and severity of arthroscopic cranial cruciate ligament (CrCL) fibre damage in dogs with cruciate rupture (CR). Design: Design Prospective clinical study. Methods: Twenty‐nine client‐owned dogs with CR underwent physical examination, stifle radiography and arthroscopy, and the findings were recorded. Initial examination was repeated after sedation and after general anaesthesia. The Spearman rank correlations of examination variables with diagnostic imaging were examined. Results: Overall, cranial tibial translation assessed by the tibial compression test in extension showed correlation with arthroscopic CrCL fibre damage (P < 0.05). Correlations between severity of cranial drawer laxity and arthroscopic CrCL fibre damage were not significant. Under general anaesthesia, stifle laxity tests were positively correlated with lameness severity grade (SR  ≥ 0.41, P < 0.05). Meniscal damage was correlated with pain on the internal rotation of the tibia (SR = 0.42, P < 0.05) and severity of radiographic osteophytosis (SR = 0.53, P = 0.01). Conclusion: Detection and estimation of severity of cranial tibial translation enable the diagnosis of CR and also the inference of the severity of CrCL fibre rupture, particularly with the tibial compression test in extension. Severity of joint laxity is best assessed under general anaesthesia. Such knowledge should reduce the risk of misdiagnosis and may enhance early diagnosis and treatment of dogs with CR over time.